E-BUSINESS-BASED ENTREPRENEURSHIP TRAINING DURING THE PANDEMIC - Bunga M. Shalihah; Muhammadinah; Kiagus Arfan (CV. Doki Course and Training, 2023)
This article discusses the understanding of MSMEs to implement E-Business to deal with declining sales due to the pandemic, The purpose of this training is to provide education and the level of awareness of MSMEs about the need for E-Business in implementing sales. The method used in this project is to use a quasi-experimental design with a pretest-posttest group design, by providing material to participants who take part in the training, then providing questionnaires to participants regarding entrepreneurial knowledge before and after the provision of material. In using E-Business, MSME training participants can utilize popular platforms such as Instagram and Facebook to promote their products with visual content such as attractive photos and videos. Meanwhile, in marketplaces such as Shopee and Tokopedia to sell products online and facilitate the transaction process for customers. In addition, by applying the concept of E-Business, MSME participants can keep up with the rapid development of technology and take advantage of the growing online business opportunities.